The Disinformation about hydroxychlorochine on Twitter: from political pressure to scientific dispute - de Araujo, Ronaldo (2020)
Introduction: Scientific disinformation has been a strong ally responsible for making it increasingly difficult to cope with the disease caused by the new coronavirus. Negative views, conspiracy theories, political opportunism are some examples of malicious use behind the dissemination of information about the virus, its effects, forms of treatment and prevention. Method: Developed through an infodemiological study, the research analyzes the sharing of information on Twitter about hydroxychloroquine, the drug that has gained prominence when talking about a possible pharmacological treatment of the disease. Data were collected via Netlytic by monitoring the hashtag #hydroxychloroquine between 11th to 30th of May and are analyzed based on the social network analysis, the understanding of frequent terms and categorization of tweets. Results: 3,714 tweets were analyzed and 2,089 users were identified. Only 678 users (32.4%) maintained connection with other users on the network. The frequent terms and their distribution indicate that the issue is played more by political aspects than by health, with a greater concentration of messages in a few users and a large number responsible for its viralization. The most common categories were "Attack on political agents" and "Disbelief in epistemic institutions". Conclusions: In the context studied, it is clear that the values of the scientific culture itself, such as recognition and authority, are gaining new informational layers in political dispute at a time when epistemic institutions are in decline.